Public Space and Housing Affairs and the dialectics of lived space - Knierbein, Sabine (Tracce urbane. Rivista italiana transdisciplinare di studi urbani, 2017)
This paper is structured into two parts. The first part is dedicated to conceptually frame “Relational Public Space and Emerging City Publics”, whereas the second part deals with “Silences and absences from public space research”: This part will deal with three case studies: Vienna, Barcelona and Berlin. The Vienna case will help to exemplify theoretical and conceptual considerations, whereas the main empirical study revolves around the Barcelona case. The Berlin case will help to translate again back from empirical findings to conceptual critique. As follows, I am planning to offer some key arguments why to combine housing activism and research, with public space activism and research. In the conclusions “Resistance combined”, I will elaborate on the core hypothesis that a dialectical bridging of segmented fields in the scrutiny of urbanization processes is needed because of constant classificatory strugglesand as an act to promote inclusive urban research.